Dreams and visions in the early Middle Ages: the reception and use of patristic ideas, 400-900 - Keskiaho, Jesse (Cambridge studies in medieval life and thought, 2015)
"Dreams and visions played important roles in the Christian cultures of the early middle ages. But not only did tradition and authoritative texts teach that some dreams were divine, some also pointed out that this was not always the case"--